NON-RESPONSE TO RESEARCH SURVEYS - Lurie, Ruth (My University, 2011)
A survey’s external validity is reliant on sample randomness and size. The sample size is the result of the minimum required and the response achieved. Much attention has been given to response in a commercial setting. Very few have examined the nature of response in academia. This study used an online questionnaire to survey researchers from 17 South African business schools. It asked about the achieved response and research design specifications. The response rate was then calculated and significance testing used, to establish which variables are the most significant in affecting response. The study concluded that the respondent characteristics, especially the industrial sector surveyed and the inclusion criteria used; an appeal based on respondets’ unique opinions; prior notice; and as short as possible a timeframe, are the most positively significant. The study makes recommendations to universities and students in increasing response and hopes to further response theory in general.
MBA - WBS
Keywords: Questionnaires; Graduate students